ANALYSIS OF BOBON SANTOSOSO'S SEMIOTICS AS A CHEF INDONESIAN PEOPLE ON TIKTOK - Wijayanti, Novita Fitri; Febriana, Poppy (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the visual signs in Bobonsantoso’s TikTok content that construct his image as the “Indonesian People’s Chef” using Charles Sanders Peirce’s visual semiotics framework, which consists of the elements Sign, Object, and Interpretant. Method: A qualitative approach was employed with visual semiotics analysis, focusing on three selected TikTok videos from 2024 categorized as Cooking with Politicians, Cooking While Sharing, and Cooking in the Archipelago, each chosen based on the highest number of views and likes. Results: The findings reveal that Bobonsantoso consistently employs visual symbols such as traditional clothing, local cultural attributes, and socially meaningful interactions. These elements not only strengthen his personal branding but also construct his image as a caring, approachable figure who values cultural heritage. Novelty: This study contributes to the understanding of how digital culinary content transcends aesthetic appeal, demonstrating the power of social media in shaping public perception, fostering solidarity, and reinforcing cultural representation, thereby legitimizing Bobonsantoso’s recognition as the “Indonesian People’s Chef.”